2011
DOI: 10.1186/1756-0500-4-535
|View full text |Cite
|
Sign up to set email alerts
|

Risky driving behaviors for road traffic accident among drivers in Mekele city, Northern Ethiopia

Abstract: BackgroundDue to its perception as a disease of development, road traffic accident and related injuries tend to be under recognized as a major health problem in developing countries. However, majority of the world's fatalities on the roads occur in low income and middle income countries. Since the main cause of road traffic accident is attributed to human risky behaviors, it is important to identify significant factors for risky behaviors of drivers.MethodsA quantitative cross-sectional study with a sample siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
48
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 11 publications
10
48
1
3
Order By: Relevance
“…Third, they draw attention to the importance of RTI prevention in Ethiopia in achieving one of the new key Sustainable Development Goals (SDGs): halving the number of RTI-related deaths and injuries by 2030. 19 Measures such as improving road safety for pedestrians (e.g., pavements, lighted cross walks and traffic lights) together with reinforcing traffic laws and legislation on the use of alcohol and khat chewing while driving (which is known to be a frequent cause for drivers' lack of attention in Ethiopia) 20 seem particularly important. …”
Section: Public Health Action Rtis In Addis Ababa Ethiopia 69mentioning
confidence: 99%
“…Third, they draw attention to the importance of RTI prevention in Ethiopia in achieving one of the new key Sustainable Development Goals (SDGs): halving the number of RTI-related deaths and injuries by 2030. 19 Measures such as improving road safety for pedestrians (e.g., pavements, lighted cross walks and traffic lights) together with reinforcing traffic laws and legislation on the use of alcohol and khat chewing while driving (which is known to be a frequent cause for drivers' lack of attention in Ethiopia) 20 seem particularly important. …”
Section: Public Health Action Rtis In Addis Ababa Ethiopia 69mentioning
confidence: 99%
“…7,21 A study conducted in Finland found that the driving style of middle-aged people was more associated with alcohol dependence; conversely, among youngsters, DUI violations were more associated with risk-taking behaviors, characteristic of this age group. 25 Furthermore, a Brazilian study investigated drinking and driving in the 27 Brazilian capitals and found that 2,410 of a total of 3,398 drivers interviewed had used alcohol over the past 12 months; of this subgroup, most were male (93.4%), drove cars or motorcycles, had a mean age of 36 years, and had completed high school.…”
Section: Discussionmentioning
confidence: 99%
“…7 Evidence has suggested that recidivists are apparently oblivious to the sanctions and penalties for drunk driving. 8 Typically, DUI recidivists are known to be predominantly young males aged between 18 and 29 years.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [15] examine the comprehension of 10 traffic signs, among other things, indicates that of the traffic signs, 5 of them were answered correctly by a majority of respondents, namely "intersection ahead". The "pedestrian crossing" traffic sign was answered correctly by 347 respondents (99%).…”
Section: Introductionmentioning
confidence: 99%